Physician wellbeing in a national rehabilitation hospital, a qualitative study utilizing Maslow’s hierarchy of needs as a framework for analysis - Áine Carroll; Claire Collins; Jane McKenzie (BMC Health Services Research)
Abstract Background Globally, healthcare systems are experiencing a workforce crisis which has been exacerbated by the COVID19 pandemic. Numerous reports have documented the deterioration of healthcare professional wellbeing with burnout being called the new pandemic. Rehabilitation Medicine Physicians are among the most likely specialties to experience burnout. There is a strong association between staff and patient experience and global and national policies and strategies have recognized the importance of ensuring staff wellbeing in healthcare organisations. Although there have been many publications on interventions focusing on wellbeing, these have been directed mainly at personal rather than organisational factors. Maslow’s hierarchy of needs, an integrated hierarchy of human needs, has been utilised as a framework to assess wellbeing in doctors but not heretofore in Rehabilitation Medicine. This study aimed to explore Rehabilitation Medicine Physician wellbeing in a complex specialist rehabilitation setting. Methods Qualitative deductive content analysis (an approach to reanalyzing existing data in a new context) was the approach used. Maslow’s hierarchy of needs was used as the categorization matrix. Qualitative data from three different data sources were systematically analysed. Results Using Maslow’s five needs (psychological, safety, social, esteem, and self-actualisation needs), the analysis demonstrated that Rehabilitation Medicine Consultants’ needs were not being met at any of the five levels. The data revealed what constitutes relative deprivation and organisational injustice. Conclusions In order to enable the flourishing of the Rehabilitation Medicine Consultants, the organisation needs to focus on satisfying not just basic needs but creating the conditions for them to function at the highest level. The adapted Maslow framework provides a scaffolding for interventions to support such flourishing.